Optimization of Glycerol-Water Extraction of Selected Bioactive Compounds from Peppermint and Common Nettle - Grażyna Kowalska; Tomasz Baj; Radosław Kowalski; Jolanta Szymańska (MDPI AG, 2021)
Current trends in the industry indicate that extraction solvents should conform with the ideals of so-called "green chemistry". Therefore, the objective of the presented study was to optimize the conditions for the extraction of polyphenols, flavonoids and chlorophyll from peppermint leaves (Mentha × piperita L., Lamiaceae) and from common nettle leaves (Urtica dioica L., Urticaceae) via green chemistry. The obtained experimental results were subjected to modelling by means of the multiple regression method, while the optimization of the system was addressed via the application of the desirability function. As a result of the use of glycerol-water systems for the extraction of the tested active compounds from mint leaves and nettle leaves, extracts with higher concentrations of polyphenols, flavonoids and chlorophyll were most often obtained, when compared with the use of classical solvents such as water and ethanol. In this work, we demonstrate that the extraction temperature has significant influence on the concentration of the determined components in the extracts. To obtain the highest values of the analysed parameters, leaves of peppermint should be extracted with glycerol-water mixture at the proportions of 30.5:69.5 at a temperature of 50 °C, while the optimal conditions for the extraction of leaves of common nettle were the glycerol-water proportions of 12.5:87.5 and extraction temperature of 20 °C. Comparing the average percentage differences between the highest values of the analysed parameters obtained in the experiment and the approximated values for various temperatures with the level of desirability, one can note a high correlation that, in the analysed examples, amounted to 0.9681. The study showed that glycerol can be an alternative solvent in the extraction of polyphenols, flavonoids and chlorophyll, replacing, e.g., ethanol-which, for various reasons, cannot always be used.